Effects of Neck Radiation Therapy on Extra-Cranial Carotid Arteries Atherosclerosis Disease Prevalence: Systematic Review and a Meta-Analysis - Bashar, Khalid (Public Library of Science, 2014)
INTRODUCTION: Radiation arteritis following neck irradiation as a treatment for head and neck malignancy has been well documented. The long-term sequelae of radiation exposure of the carotid arteries may take years to manifest clinically, and extra-cranial carotid artery (ECCA) stenosis is a well-recognised vascular complication. These carotid lesions should not be regarded as benign and should be treated in the same manner as standard carotid stenosis. Previous studies have noted increased cerebrovascular events such as stroke in this cohort of patients because of high-grade symptomatic carotid stenosis resulting in emboli. AIM: To evaluate the effect of radiation therapy on ECCA atherosclerosis progression. METHODS: Online search for case-control studies and randomised clinical trials that reported on stenosis in extra-cranial carotid arteries in patients with neck malignancies who received radiation therapy (RT) comparing them to patients with neck malignancies who did not receive RT. RESULTS: Eight studies were included in the final analysis with total of 1070 patients – 596 received RT compared to 474 in the control group. There was statistically significant difference in overall stenosis rate (Pooled risk ratio  =  4.38 [2.98, 6.45], P  =  0.00001) and severe stenosis (Pooled risk ratio  =  7.51 [2.78, 20.32], P <0.0001), both being higher in the RT group. Pooled analysis of the five studies that reported on mild stenosis also showed significant difference (Pooled risk ratio  =  2.74 [1.75, 4.30], 95% CI, P  =  0.0001). CONCLUSION: The incidence of severe ECCA stenosis is higher among patients who received RT for neck malignancies. Those patients should be closely monitored and screening programs should be considered in all patients who receive neck RT.